Digitalisasi zakat dalam repetisi donasi dengan mediasi kepercayaan dan kepuasaan: Dampak Digitalisasi Lembaga Zakat Terhadap Repetisi Berdonasi - Sepky Mardian; Luqman hakim Handoko (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to analyze the influence of digitalization of Zakat institutions on repeat donation decisions, considering the mediating roles of trust and satisfaction. The study employs the Stimulus-Organism-Response (SOR) framework approach, with the research method using Structural Equation Modeling-Partial Least Square (SEM-PLS) to examine the direct and indirect effects of digitalization in Zakat Institutions on recurring donation decisions. The analysis results show that digitalization in Zakat Institutions (DLZ) has a significant direct impact on trust (TRS) and satisfaction (ST), which subsequently drive recurring donations (RPT). However, other variables, such as program quality (KPLZ), program popularity (PPLZ), and institutional reputation (RLZ), do not significantly influence trust or satisfaction, either directly or indirectly. The mediation effects reveal that DLZ significantly affects recurring donations through trust and satisfaction, while other variables do not have a significant influence. Future research is advised to broaden the sample scope, add variables related to program quality and donor loyalty, and employ a longitudinal approach to assess the long-term effects of digitalization on recurring donations